2021
DOI: 10.3390/su13126826
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Residents’ Home Composting Intention: Integrating the Theory of Planned Behavior, the Norm Activation Model, and the Moderating Role of Composting Knowledge

Abstract: Home composting is judged as an effective municipal waste management option in which household contribution is essential, but it has a low adoption. The objectives of the study were to determine the factors that influence home composting intention and identify the moderating role of composting knowledge in the model, using the combined model of the theory of planned behavior (TPB) and norm activation model (NAM). A structured questionnaire was applied to a sample of 367 residents of Isfahan city, Iran, randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 103 publications
(151 reference statements)
4
25
0
Order By: Relevance
“…When faced with the choice of high-effort pro-environmental behaviors, individuals must invest more effort, and PC over the environment can influence the degree of individual resource investment. The outcome of SN to PEBI is consistent with the majority of studies examining tourists' pro-environmental behaviors [160][161][162][163][164]; that is, the stronger the subjective norms of tourists, the more they tend to produce varying degrees of pro-environmental behavioral intentions.…”
Section: Discussionsupporting
confidence: 80%
“…When faced with the choice of high-effort pro-environmental behaviors, individuals must invest more effort, and PC over the environment can influence the degree of individual resource investment. The outcome of SN to PEBI is consistent with the majority of studies examining tourists' pro-environmental behaviors [160][161][162][163][164]; that is, the stronger the subjective norms of tourists, the more they tend to produce varying degrees of pro-environmental behavioral intentions.…”
Section: Discussionsupporting
confidence: 80%
“…Considering the above results, the GOF was 0.493, which satisfies the 0.40 cut-off requirements for a substantial impact size (Wetzels et al, 2009). Compared with recent studies that used SRMR (Petrescu-Mag et al, 2021 and GOF (Asghar et al, 2021;Kopaei et al, 2021;Rastegari Kopaei et al, 2021) values to test the model fit, the model fit measurements of both SRMR and GOF in our study showed that our model is appropriate.…”
Section: Assessment Of the Measurement Modelsupporting
confidence: 53%
“…Although such a measure does not directly impact food waste reduction and constitutes a reactive measure to the problem, it highlights the need for better waste management, which is very stringent in Romania. Composting has economic benefits and reduces the negative environmental impact of waste [83].…”
Section: Discussionmentioning
confidence: 99%